Diagnostic yield of percutaneous computed tomography guided core needle biopsy of lung lesion and its complications in tertiary hospital - Kayastha, Prakash; Adhikari, Binaya; Suwal, Sundar; Lohani, Benu; Paudel, Sharma (International Journal of Research in Medical Sciences, 2020)
Background: Early diagnosis of lung cancer can reduce its mortality and morbidity. Minimally invasive image guided percutaneous core needle biopsy can obtain tissue sample for diagnosis and staging of lung cancer, which is crucial for correct management of lung lesions. Common complications of lung biopsy include pneumothorax, parenchymal haemorrhage and haemoptysis. The study was aimed to determine diagnostic yield and complications of the percutaneous computed tomography (CT) guided core needle biopsy of lung lesion in tertiary hospital. Methods: Hospital based prospective study was performed in 40 patients in Tribhuvan University Teaching Hospital. CT guided biopsy of lung lesions was performed with 18-gauge semi-automated biopsy instrument. The complications following the biopsy were recorded and correlated with different factors using chi-square test. Histopathology report were obtained to measure the diagnostic yield. Results: Among 40 patients who underwent guided lung biopsy, histopathology showed definitive diagnosis in 37 patients; 31 malignant and 6 benign lesions. Parenchymal haemorrhage, pneumothorax and haemoptysis were seen in 13, 8 and 5 respectively; however, none required active intervention. Emphysema in traversing lung and numbers of pleural punctures used were predictive factors of complication (p value <0.05). Conclusions: The study showed percutaneous image guided core needle biopsy has high diagnostic yield with fewer complication rates and is thus recommended for routine biopsies of lung lesions.